2020
DOI: 10.1111/codi.15252
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of CT chest in COVID‐19 diagnosis and its potential application in a surgical setting

Abstract: Aim The aim of this work was to investigate the sensitivity and utility of CT of the chest in diagnosing active SARS-Cov-2 (COVID-19) infection, and its potential application to the surgical setting. Method A literature review was conducted using Google Scholarâ and MEDLINEâ/PubMedâ to identify current available evidence regarding the sensitivity of CT chest compared with RT-PCR for the diagnosis of COVID-19-positive patients. GRADE criteria and the QUADAS 2 tool were used to assess the level of evidence. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 51 publications
1
25
0
3
Order By: Relevance
“…In this retrospective study, we found that the total lesion score of CT in severe patients was significantly higher than non-sever patients, which was consistent with previous studies showing that severe patients had a larger lung lesion area than non-severe cases [ [14] , [15] , [16] ]. This might be due to more severe bilateral pulmonary infiltrates at the peak of the disease in severe cases.…”
Section: Discussionsupporting
confidence: 91%
“…In this retrospective study, we found that the total lesion score of CT in severe patients was significantly higher than non-sever patients, which was consistent with previous studies showing that severe patients had a larger lung lesion area than non-severe cases [ [14] , [15] , [16] ]. This might be due to more severe bilateral pulmonary infiltrates at the peak of the disease in severe cases.…”
Section: Discussionsupporting
confidence: 91%
“… When dealing with positive tested COVID-19 patients, hospital planning and organization should ideally consider if surgery is emergent or elective [click here]. We recommend that in cardiac patients with clinical symptoms suggestive of infection with SARS-CoV 2 (e.g., cough, fever) and a negative PCR test result, a computerized chest tomography (CT) is performed ( 12 ). Suppose surgery is urgent and necessary in a patient with suspected or confirmed infection, before proceeding to the operating theatre.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, to enable a safe bariatric surgery program, an adequate diagnostic method to identify patients in the acute phase of COVID-19 proves critical [15]. The most commonly used diagnostic test worldwide for SARS-CoV-2 infection is RT-PCR; however, this method has failed to recognize more than 29% of asymptomatic patients [16].…”
Section: Introductionmentioning
confidence: 99%